Ultrasensitive Biosensor for the Detection of Vibrio cholerae DNA with Polystyrene-co-acrylic Acid Composite Nanospheres - Mahbubur Rahman; Lee Yook Heng; Dedi Futra; Tan Ling Ling (Nanoscale Research Letters, 2017)
Abstract An ultrasensitive electrochemical biosensor for the determination of pathogenic Vibrio cholerae (V. cholerae) DNA was developed based on polystyrene-co-acrylic acid (PSA) latex nanospheres-gold nanoparticles composite (PSA-AuNPs) DNA carrier matrix. Differential pulse voltammetry (DPV) using an electroactive anthraquninone oligonucleotide label was used for measuring the biosensor response. Loading of gold nanoparticles (AuNPs) on the DNA-latex particle electrode has significantly amplified the faradaic current of DNA hybridisation. Together with the use of a reported probe, the biosensor has demonstrated high sensitivity. The DNA biosensor yielded a reproducible and wide linear response range to target DNA from 1.0 × 10−21 to 1.0 × 10−8 M (relative standard deviation, RSD = 4.5%, n = 5) with a limit of detection (LOD) of 1.0 × 10−21 M (R 2 = 0.99). The biosensor obtained satisfactory recovery values between 91 and 109% (n = 3) for the detection of V. cholerae DNA in spiked samples and could be reused for six consecutive DNA assays with a repeatability RSD value of 5% (n = 5). The electrochemical biosensor response was stable and maintainable at 95% of its original response up to 58 days of storage period.